Sistem Pendukung Keputusan Prioritas Persediaan Tools Menggunakan Metode Fuzzy AHP - Kunthi Muslichah Ardi; Imam Husni Al Amin (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Inventory is an asset in the form of goods and equipment to support the company's operations. PT Indonesia Comnet Plus is a company engaged in telecommunications, inventory control in the company includes devices or tools used in network construction and network maintenance. In the process of determining the priority of inventory tools and monitoring the use of tools still use manual and subjective methods. Thus causing the possibility of not being precise in determining the priority of inventory tools that must be immediately in stock. The Fuzzy AHP (Analytic Hierarchy Process) method is a method that is considered better in the process of inventory management tools to the maximum. The test results prove that the fuzzy AHP method has an important level of criteria so that the resulting weight value is more detailed. The output of this system is in the form of a monitoring tools system that is equipped with a decision support system in determining the priority of the best tools inventory.